Health education actions developed in the working process of Community Health Agents (Brazilian Journal of Health Research, 2019)
Introduction:The relevance of Community Health Agents’ work in Primary Care is unquestionable. Based on the development of health education actions, these professionals contribute to the well-being of individuals, families and communities. It is essential identifying the main actions developed by them, as well as reflecting about these actions, in order to continuously improve their performance. Objective: Synthesizing health education actions developed in the working process of Community Health Agents. Methods: Integrative review conducted in data available in electronic databases such as Latin American and Caribbean Health Sciences Literature, Nursing Database and Scientific Electronic Library Online, based on controlled descriptors. Two hundred (200) articles were identified and fifteen of them composed the corpus of the current study, after they met the selection criteria. Results: Results indicate that health education actions are mainly focused on promoting oral health, overall health conditions and vaccinations, with emphasis on women’s health. Informative guidance was the main technique adopted in the analyzed studies; it was mostly focused on preventing and treating diseases and complications during home visits in the investigated communities. Conclusion: The current study contributes to the scientific and practical fields, since it gives visibility to health education actions developed by Community Health Agents.